APE1 mediates chemoresistance in esophageal squamous cell carcinoma by remodeling the immunosuppressive microenvironment - Gao, Han; Rao, Junji; Xiao, He; Kuang, Xunjie; Wang, Yong; Yao, Yujing; Yang, Yuxin; Li, Mengxia; Liao, Xiuyong; Wang, Dong (Frontiers in Immunology, 2025)
IntroductionSquamous cell carcinoma of the esophagus (ESCC) has poor prognosis after surgery and adjuvant chemotherapy. Biomarkers predicting treatment efficacy are urgently needed. This study investigated apurinic/apyrimidinic endonuclease 1 (APE1), a key DNA repair enzyme, as a prognostic biomarker in ESCC patients receiving postoperative chemotherapy.MethodsTo assess the relationship between APE1 expression and survival outcomes post-adjuvant chemotherapy. 115 ESCC patients receiving surgery and platinum-based chemotherapy were retrospectively enrolled. APE1 expression (low, medium, high) was determined by immunohistochemistry (IHC). Furthermore, external validation was performed using a tissue microarray cohort of 110 post-chemotherapy ESCC patients and the GES5325 dataset. Survival was analyzed using Kaplan-Meier and Cox regression. The tumor immune microenvironment was characterized by multiplex immunofluorescence (mIF).ResultsHigh APE1 expression correlated significantly with advanced T stage (p=0.005) and neural invasion (p=0.036). The high-expression group had significantly worse 5-year OS (27% vs. 91.4%) and DFS (14.3% vs. 55.3%) than the low-expression group (p<0.001), confirmed in public databases. Multivariate analysis identified APE1 expression (DFS: HR=4.600, 95% CI 1.285-16.466; OS: HR=16.001, 95% CI 4.826-53.061) and clinical stage as independent prognostic factors. Additionally, external validation was carried out using tissue microarrays and the GEO database to confirm the reliability. mIF analysis revealed significantly increased infiltration of FOXP3+ regulatory T cells (Treg) and cancer-associated fibroblasts (CAFs) in the APE1-high group.DiscussionHigh APE1 expression is an independent predictor of poor prognosis in ESCC patients receiving postoperative chemotherapy, associated with Treg and CAFs-mediated immunosuppression. APE1 serves as a prognostic biomarker linked to immunosuppression, enabling personalized adjuvant therapy.